Gender and the Great Experiment: ‘Feminine and Canadian Eyes’ See Soviet Women, 1926–1936 - Niergarth, Kirk (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2015)
This article focuses on the travelogues of five educated, professional, middle-class Canadian women who visited the Soviet Union in the interwar period: Alexandrine Gibb, Margaret Gould, Agnes Macphail, Margaret McWilliams, and Ella Smith. For these visitors, Soviet women were a point of emphasis, and on this subject they claimed special insight and relative expertise. Gibb, for example, offered readers a “pair of feminine and Canadian eyes and ears ready to give you mysterious Russia.” Whatever else feminine Canadian eyes saw in the USSR — for Soviet reality varied considerably between 1926 and 1936 when these women travelled — they gave Canadian audiences a more-or-less consistent impression that the great experiment was providing Soviet women opportunities denied women in Canada. This was an impression that not all Canadian audiences were prepared to accept.